Covid-19 Impact on Agricultural Farmer’s Social, Physical, and Mental Health: A Literature Review - Sulistyono, R Endro; Hayati, Nurul (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2022)
Background: COVID-19 pandemic disrupted in many business sectors and affected negatively the agricultural sector. The objectives of this review are to determine the impact of COVID-19 in the social life, physical and mental of agricultural farmer. Method: This study was a literature review. The population in the study was farmers. The process of review was; identification of literature; screening questions; eligibility using inclusion criteria; and assessment of the quality of the studies. This review was conducted by identify relevant literature, in Science Direct, PubMed, Scopus and Google Scholar using the following keywords: "Covid-19” OR "Pandemic” combined with "farmer” "farmworker” "agricultural worker”. Articles found then be charted and analysis. Result: This review found 10 articles. The finding of this review showed that COVID 19 has impacted directly on the farmer’s life both on social life, physical and mental health. Conclusion: This finding showed that farmers problems should be addressed to prevent long-term negative consequences that impair the food system and enlarge current inequalities. Also, it should be developed and implemented the appropriate community-based mental health programs targeting farmers who impacted by pandemic and who are at risk to develop adverse mental health outcomes.